2019
DOI: 10.3390/ijms20174188
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Phosphoinositide 3-Kinase/Protein Kinase B Signaling Hampers the Vasopressin-dependent Stimulation of Myogenic Differentiation

Abstract: Arginine-vasopressin (AVP) promotes muscle differentiation, hypertrophy, and regeneration through the combined activation of the calcineurin and Calcium/Calmodulin-dependent Protein Kinase (CaMK) pathways. The AVP system is impaired in several neuromuscular diseases, suggesting that AVP may act as a physiological factor in skeletal muscle. Since the Phosphoinositide 3-kinases/Protein Kinase B/mammalian Target Of Rapamycin (PI3K/Akt/mTOR) signaling plays a significant role in regulating muscle mass, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
(101 reference statements)
0
4
0
1
Order By: Relevance
“…Sergio's main research interests were focused on muscle homeostasis and regeneration under normal and pathologic conditions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The most relevant results obtained by Sergio and his collaborators indicate novel functions for the neurohypophyseal hormones, vasopressin (AVP) and oxytocin (OT), which regulate skeletal muscle differentiation, trophism, and homeostasis. In particular, Sergio's group demonstrated for the first time that AVP promotes muscle differentiation, hypertrophy, and regeneration through the combined activation of the calcineurin and Calcium/Calmodulin-dependent Protein Kinase (CaMK) pathways.…”
Section: Sergio Adamo Full Professor In Histology Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Sergio's main research interests were focused on muscle homeostasis and regeneration under normal and pathologic conditions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The most relevant results obtained by Sergio and his collaborators indicate novel functions for the neurohypophyseal hormones, vasopressin (AVP) and oxytocin (OT), which regulate skeletal muscle differentiation, trophism, and homeostasis. In particular, Sergio's group demonstrated for the first time that AVP promotes muscle differentiation, hypertrophy, and regeneration through the combined activation of the calcineurin and Calcium/Calmodulin-dependent Protein Kinase (CaMK) pathways.…”
Section: Sergio Adamo Full Professor In Histology Andmentioning
confidence: 99%
“…Indeed, by upregulating the regeneration/differentiation markers, modulating the inflammatory response, and attenuating fibrogenesis, the stimulation of AVPdependent pathways creates a favorable environment for efficient and sustained muscle regeneration and repair even in the presence of elevated levels of the inflammatory cytokine TNF. [10][11][12][13][14][15] All these studies performed by Sergio's group highlight a novel in vivo role for AVP-dependent pathways, which may represent an interesting strategy to counteract muscle decline in aging or in muscular pathologies. 13 All of the above prompted to verify whether neurohypophysial hormones might be proposed as a hormonal treatment to counteract cancer-induced muscle wasting, as well.…”
Section: Sergio Adamo Full Professor In Histology Andmentioning
confidence: 99%
“…This pathway is recruited in response to NH in myoblasts, and its inhibition hampered the AVP-stimulated expression of both Akt and mTOR and increased the expression of the ubiquitin ligase atrogin-1 and FoxO (Figure 1). 11 Satellite cells obtained from aged mice display lower OT receptor expression and myogenic potential when compared to satellite cells from young animals. By treating the "old" and "young" satellite cells with exogenous OT or with a selective oxytocin antagonist, respectively, OT was demonstrated to be required for effective muscle regeneration.…”
Section: Skeletal Muscle Is a Target Of Avp And Otmentioning
confidence: 99%
“…After binding to the receptors, AVP exhibits its biological effects through a series of cascade reactions: V1a receptor activates phospholipase C by coupling with G protein to induce the release of intracellular calcium ions, thus affecting blood vessel constriction and liver glycogen decomposition [7] ; V2 receptor activates guanylate-binding protein to increase the expression of aquaporin-2 in the inner lining of renal collecting duct through cyclic adenosine-dependent pathway, and promotes the reabsorption of free water by the kidney [8] . It has been reported that AVP in myogenic cells activates the calcineurin (CaN) pathway through V1aR to affect the phosphorylation of downstream nuclear factor of activated T cells (NFAT), thus affecting the transcription of downstream regulatory genes [9] . It was also reported that the activated CaN-NFAT signaling pathway affects cardiac hypertrophy, and the transcriptional activation of NFAT family members regulates the central processes of HF [10] .…”
Section: Introductionmentioning
confidence: 99%